Investigation of starting tension of alfalfa and bitter cane seeds in the interelectrode space of electric cleaner - Yusubaliev Ashirbay; Sharipov Sherzod Nasim (Genius Journals, 2023)
Based on the basic properties of alfalfa seeds, the article substantiates the constructive scheme of their cleaning from seeds of quarantine plants. For sorting and cleaning of alfalfa seeds the constructive scheme consisting of concentric cylindrical electrodes with increasing intensity of electric field in the direction of seed movement has been adopted.
Keywords: Alfalfa; weed plants; seeds; properties; cleaning